Supramolecular self-assembled nonlinear optical molecular glasses with enhanced electro-optic activity and alignment stability. (June 2022) - Gu, Caiqin; Huang, Zeling; Rahman, Abdul; Chen, Xunyu; Zeng, Ziying; Liang, Zhiwei; Shi, Lei; Liu, Fenggang; Wang, Jiahai
Abstract: We have developed a series of self-assembled electro-optic dendrimers. Four dendrimers H1, H2, H3 and HLD 1 were synthesized by introducing aromatic dendron (HD), trifluorobenzyl dendron (TFD), pentafluorophenyl dendron (PFD) and anthracene ring (AH) into the donor and bridge parts of chromophores. In addition, three-arm trifluorobenzyl dendron containing multichromophore H4 was also synthesis and evaluated. These molecules were supramolecular self-assembled through the π-π interaction of HD-PFD/HD-AH/TFD-TFD to minimize the dipole-dipole interaction of chromophores and maximize the accentric order of chromophores under high load densities. High r33 (328, 317 and 279 p.m./V) have been achieved for neat films containing chromophores 1:1 H1 : H3, 1:2 H3 : HLD 1 and H4, respectively. Moreover, the long-term orientation stability of chromophores were also improved. After 1000 h at room temperature, the initial electro-optic coefficient of the electrode self-assembled film still remains above 95%. Graphical abstract: Image 1 Highlights: Four chromophores with different modified isophorone-derived bridge had been synthesized. At 1310 nm, the r33 value of three best films are 328, 317 and 279 pm/V, respectively. The decomposition temperatures of synthesized chromophores are higher than 270 °C. The initial electro-optical coefficient of the electrode film can be maintained above 95% after 1000 h.